The Role of Project Management Practices in Achieving Quality Delivery in Public Sector Projects (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The impact of project management practices in achieving quality delivery in public sector projects is the target focus of research scholars. This trend of study is subjected to an investigation of the role of project management practices in achieving quality delivery in public sector projects, particularly within Bayelsa State, Nigeria. Thus, the presentation of this paper is one of such using SPSS software for the data analysis. This study involves the collection of empirical data, primarily through a structured Likert-scale questionnaire. The methodological approach adopted was a descriptive survey design, within a quantitative research framework. To examine the influence of the independent variables on the dependent variable, Multiple Regression Analysis (MRA) was employed. The findings from the data analysis reveal a substantial 75% correlation between the independent and dependent variables, accompanied by a coefficient of determination (R-squared) of 0.563, or 56.3%. In addition, the analysis yielded a highly statistically significant p-value (p < 0.001). These results collectively depicts that the predictive model, involving six independent variables such as project planning, resource management, risk management, monitoring/evaluation, stakeholder engagement, and the utilization of project management tools/methodologies, is highly significant in predicting the role of project management practices in achieving quality delivery in public sector projects.